La Gamificación y el proceso de enseñanza aprendizaje de la factorización en los estudiantes de noveno año de educación general básica - Cifuentes Macias, Juan Carlos (2025)
This study, entitled “Gamification and the Factoring Learning Process in Ninth-Grade Students at the Amelia Gallegos Educational Institution,” aimed to identify the gamification strategies used in factoring learning at the Amelia Gallegos Educational Unit during the 2024-2025 academic year. A non-experimental, descriptive, field-based, cross-sectional design with a quantitative approach was employed. Data was collected through a questionnaire and an objective test, and the results were analyzed using Microsoft Office Excel. The findings revealed that gamification is used sometimes or rarely in factoring classes. Furthermore, when asked if they would like to receive gamified lessons, over 73.33% of the students stated that they would like to use playful activities; however, approximately 60% indicated that their understanding and practice of factoring remains limited, highlighting the need for more robust and situation-oriented lesson planning. Practical applications. It is suggested that gamification be used in teaching factorization, carefully planned, integrating clear objectives, curricular content, and meaningful game dynamics. Furthermore, it should be combined with teaching strategies that promote reflection, practice, and conceptual understanding, ensuring that the game reinforces deep learning and active participation